Volume of Solids of Revolution

Calculus Level 4

Let e e be Euler's number and x > 1 x > -1 .

Let f ( x ) = lim n j = 1 n ( j n ) n ( 1 e x ) n j f(x) = \lim_{n \rightarrow \infty} \sum_{j = 1}^{n} (\dfrac{j}{n})^n (\dfrac{1}{e^x})^{n - j} and g ( x ) = 1 a x + b g(x) = \dfrac{1}{ax + b} .

If g ( 0 ) = f ( 0 ) g(0) = f(0) and g ( 1 ) = f ( 1 ) g(1) = f(1) , find the volume of the region bounded by the two curves f ( x ) f(x) and g ( x ) g(x) on [ 0 , 1 ] [0,1] when revolved about the x x -axis to seven decimal places.


The answer is 0.2854552.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rocco Dalto
Jul 12, 2018

f ( x ) = lim n j = 1 n ( j n ) n ( 1 e x ) n j = f(x) = \lim_{n \rightarrow \infty} \sum_{j = 1}^{n} (\dfrac{j}{n})^n (\dfrac{1}{e^x})^{n - j} = lim n j = 0 n 1 ( 1 j n ) n ( 1 e x ) j = \lim_{n \rightarrow \infty} \sum_{j = 0}^{n - 1} (1 - \dfrac{j}{n})^n (\dfrac{1}{e^x})^{j} = j = 0 ( 1 e x + 1 ) j = e x + 1 e x + 1 1 \sum_{j = 0}^{\infty} (\dfrac{1}{e^{x + 1}})^j = \dfrac{e^{x + 1}}{e^{x + 1} - 1} on x > 1 x > -1 .

Let g ( x ) = 1 a x + b g(x) = \dfrac{1}{ax + b} .

g ( 0 ) = f ( 0 ) = e e 1 b = e 1 e g(0) = f(0) = \dfrac{e}{e - 1} \implies b = \dfrac{e - 1}{e} and g ( 1 ) = f ( 1 ) = e 2 e 2 1 a = e 1 e 2 g ( x ) = e 2 ( e 1 ) ( x + e ) g(1) = f(1) = \dfrac{e^2}{e^2 - 1} \implies a = \dfrac{e - 1}{e^2} \implies g(x) = \dfrac{e^2}{(e - 1)(x + e)} .

Let I 1 = π 0 1 ( f ( x ) ) 2 d x = π 0 1 ( e x + 1 e x + 1 1 ) 2 d x I_{1} = \pi\int_{0}^{1} (f(x))^2 dx = \pi\int_{0}^{1} (\dfrac{e^{x + 1}}{e^{x + 1} - 1})^2 dx .

Let u = e x + 1 d x = 1 u d u u = e^{x + 1} \implies dx = \dfrac{1}{u} du \implies

I 1 = π e e 2 u ( u 1 ) 2 d u I_{1} = \pi\int_{e}^{e^2} \dfrac{u}{(u - 1)^2} du

Let w = u 1 d w = d u I 1 = π e 1 e 2 1 w + 1 w 2 d w = π e 1 e 2 1 1 w + w 2 d w = π ( ln ( w ) 1 w e 1 e 2 1 ) = w = u - 1 \implies dw = du \implies I_{1} = \pi\int_{e - 1}^{e^2 - 1} \dfrac{w + 1}{w^2} dw = \pi\int_{e - 1}^{e^2 - 1} \dfrac{1}{w} + w^{-2} dw = \pi(\ln(w) - \dfrac{1}{w}|_{e - 1}^{e^2 - 1}) =

π ( ln ( e + 1 ) + e e 2 1 ) \pi(\ln(e + 1) + \dfrac{e}{e^2 - 1})

I 2 = π 0 1 ( g ( x ) ) 2 d x = e 4 π ( e 1 ) 2 0 1 ( x + e ) 2 d x = I_{2} = \pi\int_{0}^{1} (g(x))^2 dx = \dfrac{e^4\pi}{(e - 1)^2}\int_{0}^{1} (x + e)^{-2} dx =

e 4 π ( e 1 ) 2 ( 1 x + e ) 0 1 = -\dfrac{e^4\pi}{(e - 1)^2}(\dfrac{1}{x + e})|_{0}^{1} = π e 4 ( e 2 1 ) ( e 1 ) e \dfrac{\pi e^4}{(e^2 - 1)(e - 1)e}

\implies the volume V = π 0 1 ( g 2 ( x ) f 2 ( x ) ) d x = π ( e ( e 2 e + 1 ) ( e 2 1 ) ( e 1 ) ln ( e + 1 ) ) 0.2854552 V = \pi\int_{0}^{1} (g^2(x) - f^2(x)) dx = \pi(\dfrac{e(e^2 - e + 1)}{(e^2 - 1)(e - 1)} - \ln(e + 1)) \approx \boxed{0.2854552}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...